2021
DOI: 10.18502/kls.v6i1.8660
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with the Implementation of Patient Safety at X Hospital, Karawang, Indonesia

Abstract: Patient safety is a significant global health problem and a top priority for incidents prevention. Data revealed that the patient safety goals’ average implementation was only 33.5%, far away from the 100% target. The compliance of hand hygiene among nurses, meanwhile, was only 28.6%. This study aims to analyze factors associated with the implementation of patient safety goals among nurses at X Hospital Karawang. A cross-sectional approach with a simple random sampling technique was implemented in this study. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 0 publications
0
4
0
2
Order By: Relevance
“…Makalah lain juga melakukan penelitian di rumah sakit, yang memberikan hasil bahwa pengetahuan, pengawasan, motivasi, dan pelaksanaan tujuan keselamatan pasien (pvalue < 0,05). (Suryani et al,2021). Makalah yang lain yang juga ditemukan menunjukkan adanya pengaruh pengawasan, karakter figur otoritas dan rekan kerja yang tidak patuh berpengaruh terhadap keputusan perawat untuk melaksanakan keselamatan pasien.…”
Section: Mekanisme Seleksi Artikelunclassified
“…Makalah lain juga melakukan penelitian di rumah sakit, yang memberikan hasil bahwa pengetahuan, pengawasan, motivasi, dan pelaksanaan tujuan keselamatan pasien (pvalue < 0,05). (Suryani et al,2021). Makalah yang lain yang juga ditemukan menunjukkan adanya pengaruh pengawasan, karakter figur otoritas dan rekan kerja yang tidak patuh berpengaruh terhadap keputusan perawat untuk melaksanakan keselamatan pasien.…”
Section: Mekanisme Seleksi Artikelunclassified
“…Hasil penelitian mengambarkan penerapan keselamatan pasien oleh perawat sebagai berikut. (Neri, Lestari and Yetti, 2018); penerapan sasaran keselamatan pasien 94% baik (Suryani, Kurniawan and Perdani, 2021).…”
Section: Penerapan Sasaran Keselamatan Pasienunclassified
“…The study results showed there was a significant relationship between knowledge and the implementation of the 6 patient safety goals (p = 0.002) (Pambudi, 2018). In addition, according to Suryani et al (2021), nurses' knowledge is related to the patient safety goals application (p = 0.038), nurses with high knowledge implement patient safety goals better than nurses with moderate and low knowledge. According to Nurmaini et al (2021), Nursing care knowledge and education have a positive correlation on the application of patient safety goals.…”
Section: Internal Factors That Affect the Implementation Of Patient Safety Goalsmentioning
confidence: 99%
“…In the category of implementing good safety targets, 36 (29.0%) respondents had less supervision, and 54 (43.5%) had good supervision. Similarly, according to Suryani et al, (2021), Supervision from head nurses will influence 8.5 times for nurses to achieve patient safety goals. Supervision is a way to build professional interaction and communication between nursing supervisors and implementing nurses.…”
Section: External Factors That Affect the Implementation Of Patient Safety Goalsmentioning
confidence: 99%
See 1 more Smart Citation